Metro Sistemlerinin Tasarımında Yapım Ve İşletme Maliyetlerinin Optimizasyonu İçin Bir Yaklaşım - Dündar, Mehmet Tarık (Fen Bilimleri Enstitüsü, 2016)
Ülkemizde raylı sistemlere önem verilmeye başlanmış olmasına karşın, henüz ülke geneli için gelinen nokta yetersizdir. Uzun yıllar karayoluna yatırım yapılmış, kent içi raylı sistemler ve şehirler arası demiryolları ihmal edilmiştir. Ulaştırma yatırımları uzun dönemli etkileri olan yüksek maliyetli yatırımlardır. Bu nedenle bu tür büyük altyapı projelerine ilişkin önceliklerin doğru belirlenmesi ve kısıtlı ekonomik kaynakların en fazla yarar getirecek biçimde kullanılması çok önemlidir. Dolayısıyla yanlış kararlarla oluşturulan herhangi bir ulaştırma projesinin daha sonra yapılacak ulaştırma yatırımlarının yerini ve biçimini bağlayıcı etkileri vardır. Kent yönetimleri ulaşım altyapısı yapım kararı alırken, sistemin ekonomik olmasına da gereken önemi vererek, özenle karar vermek zorundadır. Bu çalışmanın amacı, ilk yapım maliyeti yüksekliği başlıca problemlerinden biri olan raylı toplu taşıma sistemlerinden özellikle metro sistemleri yatırımlarında, yapım ve işletme maliyetlerinin, farklı yolculuk kapasiteleri, çeşitli yapım metotları, farklı dizi uzunluklarına vb. değişkenlere göre hesaplanarak en uygun yapım ve işletme maliyet alternatiflerini öneren bir yaklaşım metodu geliştirmektir. Bu amaçla, metro sistemlerinin yapımı öncesi hazırlanan fizibilite etüdü çalışmasına esas olacak, en uygun yapım ve işletme maliyetlerini sağlayan sistemleri öneren bir yazılım geliştirilmiştir. Bu yazılımda söz konusu metro hattının yapım ve işletme maliyetinin birlikte optimize edilmesi sırasında BP-BB genetik algoritma yöntemiyle metro hattı için oluşabilecek düşey profiller içinde en uygunu belirlenecektir. Geliştirilen yaklaşım metodunun evrensel olması amaçlanmış olup, ayrıca bölgeye ve zamana göre güncelleme imkânına sahip olması da amaçlanmıştır. Dünyanın herhangi bir yerinde yapılacak bir metro sistemi yatırımının, yerel yapım ve işletme koşulları, tez çalışması içindeki modele işlendiğinde o bölge için de en uygun yapım ve işletme alternatiflerini kent yöneticisine sunabilecektir. Bu çalışma sayesinde, bir çok sistem alternatifinin ilk yapım maliyeti ve 20 yıllık işletme maliyetinin hesaplanması, o sistemin şehrin genel ağı içerisindeki gelecekteki konumunu da göz önüne alan en uygun maliyetli sistemin önerilmesi, kentin kaynaklarının doğru kullanılmasının sağlanması hedeflenmektedir. Tezin literatür taramasını takip eden ikinci bölümünde raylı sistemlerin proje aşamaları ve sistemler hakkında genel bilgi verilmiştir. Üçüncü bölümde ise metro sistemlerinin ilk yapım maliyetini oluşturan, hat ve istasyon yapılarının yapım yöntemleri anlatılmıştır. Devamında metro sistemlerinin yapım ve işletme maliyeti analizi çalışmaları incelenmiş ve geliştirilen yazılım ve simülasyon programı hakkında bilgi verilmiştir. Daha sonra metro optimizasyonu için hazırlanan yazılımının örnek bir hat üzerinde uygulaması ve çeşitli alternatiflerin denenmesi ile elde edilen sonuçlar değerlendirilmiştir.

Transport is an indispensable part of the lives of people, but also it is one of the main problem areas in any urban region. It is a problem because “vehicle registrations are growing fast on the basis of increased populations, increased wealth, increased commercial penetration, and probably an increasingly persuasive picture in the developing world of international lifestyle in which a car is an essential element” (Gakenheimer, 1999). The public transportation system is the best method to meet the transportation demands in a city. Metro systems considered important in Turkey but on the other hand it has not reached to the desired level. Investments are mostly oriented to the roadways and rubber-tired PT systems in Turkey up to 2000s, urban rail systems have been largely neglected. Notwithstanding its crucial advantages, metro systems have also certain disadvantages, chiefly capital costs and long periods of implementation. Therefore, it is highly critical to adopt the right decisions before deciding or implementing metro system investments. Any transportation project created with the wrong decision will affect other transportation investment's location and form. Systems are considered in the feasibility studies that organized before the construction of metro systems. During the feasibility studies conducted prior to the civil works stage, planners take into account the most feasible options that ensure optimal construction and operating costs. Estimated volume of ridership is the most important input affecting the entire system architecture in metro projects (Demircan, K., 2010). In this respect, it is essential to minimize the estimation errors in feasibility studies, since the errors have a direct impact upon the revenues, and hence profitability of the operations. Each subsystem should be designed not only with the minimum cost but it should also meet the demand capacity. Stations have a substantial share in the construction cost of a system,therefore it is crucial to plan and locate stations correctly. Feasibility studies play a crucial role in urban rail systems for the investment decisions. In feasibility studies, the construction costs and the travel demand estimates should be close to the actual values (or the realized values). Nowadays, there are many discrepancies between the estimated values and the realized (or actual) values. Flyvbjerg has found that large percentages of demand and cost forecast have error in his research on 210 feasibility study of the rail system. (Flyvbjerg,2003) There are also many mistakes in the feasibility studies for estimating construction costs of the metro system. Some of these discerapancies are due to the use of aggregate costs calculated from the past or other city’s data. The aim of this software to gain, the transport demand for the target year, as well as to ensure minimum construction and operating costs. The basis of criteria of this such as different ridership capacities, various construction methods, different lengths for train series etc., it tries to construct a methodology proposing optimal construction and operation scenarios. Furthermore, this study aims to offer; proposed software model must meet the estimated transport demand for the target year and also satisfies minimum construction and operating costs with alternatives for the feasibility studies. In this study, an optimization model, that utilizes the output of travel demand analysis and other design criteria, is improved for a new subway system. The software should offer vertical profiles for the metro line and station type selections with an alternative proposal, which should be expected the most economical. A cost library was established from the ongoing and finished construction cost of the metro stations in Istanbul. In addition, this cost library should be modified for any city for future certain items. Metro operation costs for Istanbul city were analyzed to gain metro operation cost for per square meter and vehicle-km values. Detailed information about values and formulas will be given mentioned PhD Dissertation. Travel demand results that have been prepared for the proposed metro alignment corridor and other variable data of this region are the inputs of the cost optimization software. Alternative longitudinal profiles shall be offered according to the light of vertical design criteria and it presents the appropriate station types and track types by the algorithms. This software shall suggest total construction cost of the optimum metro system. These recommendations shall be found based on each type of construction costs between 4-8 vehicles in a train set. Construction methods of the metro line and stations are described in the below articles. There are also many cost differences for construction and operating costs of the Metro systems from country to country. It varies even from city to city, even within the same country. The construction and operating costs in each city are determined by the city's own terms. Istanbul city’s data has been used for the mentioned software for construction and operation of metro systems. These cost and area functions are given in the below articles. The average construction costs of the latest constructions of the existing Metro systems in Istanbul were used in the mentioned optimization software. Unit construction costs per $m^{2}$ were derived from civil works and electromechanical systems cost analysis of Kadikoy -Kartal metro system. Operation costs include mainly staff, energy and maintenance costs. The operation outputs of Metro Istanbul (Former name: Istanbul Ulasim Company) that is the operator of Istanbul metro system were investigated for this purpose. The most important components of the metro system’s operation have analyzed in the scope of this study. In order to optimize the construction and operation costs of a metro line, a software was developed in Microsoft Visual Studio with $C\#$ language by using object oriented programming approach. The software uses Big Bang - Big Crunch algorithm for the optimization process. Cost optimization program was prepared utilizing an energy simulation program and via optimization algorithm. Consumed energy of the metro trains was obtained from the functions based on the multi-train simulator’s output. Train operation and movements were simulated in Simulator X software. Movement between the two stations for a train set consisting 6-car with AW3 load was simulated Simulator X using for different values of the distance and slope. Simulator X (or shortly SimuX) is a multi-line, multi-train simulation program for electrified rail transportation systems. SimuX enables user to simulate transportation systems in great detail and flexibility. It is under continuous development with new features as per new needs and developments emerge in the sector. In order to optimize the construction and operation costs of a metro line, a software was developed in Microsoft Visual Studio with \texttt{C\#} language by using object oriented programming approach. The software uses Big Bang - Big Crunch (BB-BC) algorithm for the optimization process. BB-BC Genetic Algorithm method and Results of the Simulator X were used for the optimization. This software shall be used as basis source for the feasibility studies done for metro systems. Finally, the study aims to offer; proposed software model must meet the estimated transport demand for the target year and also satisfies minimum construction and operating costs with alternatives. Working mechanism of the cost optimization software can be summarized as follows. Firstly, input values shall be loaded into the program. Inputs: Location information of the station, from GIS The number of passengers arriving at the station, from Travel Demand Analysis Station construction method (CM) proposal, if it is known Platform \& Switch CM proposal, if it is known Constrains for the proposed metro line, if it is known Cost Information (2nd phase for other countries). The software processes the data at hand in accordance with the design criteria and standards. Primarily, vertical profile design process starts according to existing ground levels. Secondly, bottom and top level of the constraints of the vertical profile values are handled by the software. If there is no information given by the user in the depth of the line then the subsequent stations will be established according to the position of the alternate longitudinal section. Cost optimization starts after this stage. The cost values of the elements of the metro system can be derived from the library cost. These alternative longitudinal profiles will be offered according to the light of vertical design criteria and it presents the appropriate station types and track types by the algorithms described above. Herewith total construction cost of the optimum metro system will be offered by this software. These recommendations will be found based on each type of construction costs between 4-8 vehicles in a train set. As mentioned above, the operating costs will be found under three titles. Simux outputs will be utilized especially to find the energy consumption values of the metro vehicles, according to the characteristics of the metro line. In addition, operating cost (energy) values of all alternative profiles will be calculated. Herewith total construction cost of the optimum metro system will be offered by this software. These recommendations will be found based on each type of construction costs between 4-8 vehicles in a train set. As mentioned above, the operating costs will be found under three titles. Simux simulation program outputs will be utilized especially to find the energy consumption values of the metro vehicles, according to the characteristics of the metro line. In addition, operating cost values of all alternative profiles will be calculated. According to the results of the optimization software, total energy consumption of the metro system will be determined for various operating methods. Station operating cost values will be calculated according to system needs additionally. Optimization result for the vertical design can be shown in the Figure 1. Finally, general operation costs will be added to this calculation. In this manner, the overall operating cost will be found. For comparing each operation methods in healthy way, operating costs will be calculated for a period of 20 years for the feasibility study. Operation costs calculated for 20 years, because of heavy maintenance (renovation of the facilities) process start for the installations after this year. Heavy maintenance for the installations is not added to the operation costs. The most appropriate construction and operating costs will be proposed for all alternatives according to the different operation methods at the end of the optimization process. As a result of this optimization for the rail system being studied, the output of the program is as follows; System design criteria Vertical geometry design criteria Station sizing design criteria (according to the type of system) System business metrics Approximate cost analysis for the metro system. Outlined in the section above all as a result of this process, the available software creates results by optimizing their suggestions. Design parameters of the proposed metro system Metro system operation plan proposal Municipalities, Contractors and Consultants can use these outputs in preliminary design stage. Alignment designer can use vertical profile primarily and architect can design their stations according the results obtained from the software. Establishing metro system in any city requires a long process of decision-making, and because of this, there can be many modifications in the projects from the beginning. Transport investments have long lasting effects on economic, social and physical life of cities, and this is particularly true for rail transit investments, which have fixed infrastructure resulting in a permanent change in urban areas. This fixed infrastructure also makes rail transit projects extremely expensive investments. Rapid rail transit systems require the highest amount of investment costs. Considering the high cost involved in the development of these systems, it is particularly important that their performance justifies this high cost and that expectations from these investments are meet. Detailed cost optimization should be done for metro systems before taking construction decisions. Looking at the M4 Metro system as an example (Istanbul), this system has an 8 car train set system with 70.000 pphpd (Passenger per hour per Direction) capacity. However, this system carries a maximum of 250,000 passengers per day. In this line’s feasibility study, total demand was estimated at approximately one million passengers after 20 years operation start in the feasibility. It is not known when it will use all of its capacity. Because these lines are extending, but also parallel, lines connecting to this line will be established in the future network plan. It is possible that this line will never use its full capacity. This software will be beneficial for the policy of establishing metro systems for the city’s decision makers and will be eligible to make every difference on the model and the parameters. Retrieving closest values to the actual total cost from the output of the established software was one of the targets in this study. These values can be used also in the feasibility study. Furthermore, outputs produced by this software should be used as a base design for the all project stages. In this study outlined thesis is targeted to be completed in the second half of 2015. This software will provide the results of cost optimization as shown in the above figures and following table. As a result, and looking from economical point of view, choosing shorter metro systems will become more reasonable for countries who have financial concerns and whose future development plans are ever-changing like Turkey.
An Approach For Optimizing Construction And Operation Costs Of Metro Systems
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: Metro; yapım maliyeti; işletme maliyeti; optimizasyon; tasarım; Metro; construction cost; operation cost; optimization; design